SIMÓN BOLÍVAR’S REPUBLIC: A BULWARK AGAINST THE “TYRANNY” OF THE MAJORITY - Helg, Aline (Revista de Sociologia e Política, 2012)
Based on Bolívar’s speeches, decrees, and correspondence as well as on Gran Colombia’s constitutions and laws, this essay examines the tensions within Bolívar’s vision of Venezuela’s and New Granada’s society produced by his republican, yet authoritarian and hierarchical ideas, his concern for keeping the lower classes of African descent in check, and his denial of Indian agency. It shows that even in Peru, Bolívar’s main concern was to prevent the racial war and social disintegration that allegedly slaves and free Afrodescended people would bring to the newly independent nations. To prevent such an outcome, he advocated all along legal equality through the abolition of the colonial privileges and, since mid-1816, the abolition of slavery, but simultaneously the preservation of the monopole of power by the white creole elite. He secured the perpetuation of the socioracial hierarchy inherited from Spain by a two-edged citizenship: an active citizenship restricted to a tiny literate and skilled minority and an inactive citizenship for the immense majority of (mostly nonwhite) men.